Mitoquinone mesylate as post-exposure prophylaxis against SARS-CoV-2 infection in humans: an exploratory single center pragmatic open label non-randomized pilot clinical trial with matched controlsResearch in context - Keren Chen; Nicholas J. Jackson; Theodoros Kelesidis (EBioMedicine, 2024)
Summary: Background: An ongoing important need exists to rapidly develop novel therapeutics for COVID-19 that will retain antiviral efficacy in the setting of rapidly evolving SARS-CoV-2 variants and potential future development of resistance of SARS-COV-2 to remdesivir and protease inhibitors. To date, there is no FDA-approved treatment for post-exposure prophylaxis against SAR-CoV-2. We have shown that the mitochondrial antioxidant mitoquinone/mitoquinol mesylate (Mito-MES), a dietary supplement, has antiviral activity against SARS-CoV-2 in vitro and in SARS-CoV-2 infected K18-hACE2 mice. Methods: In this exploratory, pragmatic open label clinical trial (ClinicalTrials.gov identifier NCT05381454), we studied whether Mito-MES is an effective post-exposure prophylaxis treatment in people who had high-grade unmasked exposures to SARS-CoV-2 within 5 days prior to study entry. Participants were enrolled in real-world setting in Los Angeles, United States between May 1 and December 1, 2022 and were assigned to either mito-MES 20 mg daily for 14 days (n = 40) or no mito-MES (controls) (n = 40). The primary endpoint was development of SARS-CoV-2 infection based on 4 COVID-19 diagnostic tests [rapid antigen tests (RATs) or PCR] performed during the study period (14 days post exposure). Findings: Out of 40 (23 females; 57.5%) study participants who took Mito-MES, 12 (30%) developed SARS-CoV-2 infection compared to 30 of the 40 controls (75%) (difference −45.0%, 95% confidence intervals (CI): −64.5%, −25.5%). Out of 40 (19 females; 47.5%) study participants in the control group, 30 (75.0%) had at least one positive COVID-19 diagnostic test and 23 (57.5%) were symptomatic. With regards to key secondary outcomes, among symptomatic SARS-CoV-2 infections, the median duration of viral symptoms was lower in the Mito-MES group (median 3.0, 95% CI 2.75, 3.25) compared to the control group (median 5.0, 95% CI 4.0, 7.0). None of the study participants was hospitalized or required oxygen therapy. Mito-MES was well tolerated and no serious side effect was reported in any study participant. Interpretation: This work describes antiviral activity of mito-MES in humans. Mito-MES was well tolerated in our study population and attenuated transmission of SARS-CoV-2 infection. Given established safety of Mito-MES in humans, our results suggest that randomized control clinical trials of Mito-MES as post-exposure prophylaxis against SARS-CoV-2 infection are warranted. Funding: This work was supported in part by National Institutes of Health grant R01AG059501 (TK), National Institutes of Health grant R01AG059502 04S1 (TK), NIH/National Center for Advancing Translational Sciences (NCATS) UCLA CTSI Grant Number UL1TR001881 and California HIV/AIDS Research Program grant OS17-LA-002 (TK).